Dual Regulation of Tank Binding Kinase 1 by BRG1 in Hepatocytes Contributes to Reactive Oxygen Species Production - Lv, Fangqiao; Shao, Tinghui; Xue, Yujia; Miao, Xiulian; Guo, Yan; Wang, Yutong; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Excessive accumulation of reactive oxygen species (ROS) is considered a major culprit for the pathogenesis of non-alcoholic fatty liver disease (NAFLD). We have previously shown that deletion of Brahma related gene 1 (BRG1) mitigated NAFLD in mice in part by attenuating ROS production in hepatocyte. Here we report that BRG1 deletion led to simultaneous down-regulation in expression and phosphorylation of tank binding kinase 1 (TBK1) in vivo and in vitro. On the one hand, BRG1 interacted with AP-1 to bind to the TBK1 promoter and directly activated TBK1 transcription in hepatocytes. On the other hand, BRG1 interacted with Sp1 to activate the transcription of c-SRC, a tyrosine kinase essential for TBK1 phosphorylation. Over-expression of c-SRC and TBK1 corrected the deficiency in ROS production in BRG1-null hepatocytes whereas depeltion of TBK1 or c-SRC attenuated ROS production. In conclusion, our data suggest that dual regualtion of TBK1 activity, at the transcription level and the post-transcriptional level, by BRG1 may constitute an important mechanism underlying excessive ROS production in hepatocytes.